WalkNRide: contextualising feedback in physical activity trackers - Barros, Sérgio Manuel Nóbrega de (2015)
Increasing levels of sedentarism and obesity, along with advances in sensor technologies have instigated a market for wearable activity trackers, electronic devices that sense users’ physical activity levels with the goals of self-monitoring and behaviour change. Nowadays, activity trackers are one of the most desirable technologies, making up for a market of over $230 million in 2013. However, despite the spike of users’ interest, activity trackers have been shown to lose their appeal over time, with a recent survey suggesting that one out of three users discard the tracker in the course of the first six months of use. The question we pose is: how can we design activity tracker so that users’ interests is sustained over the long term? Our design approach focuses on contextualising physical activity. We do this through sensing users’ locations and activities (such as being still, walking or commuting through a car, bus or other means) and thus providing innovative ways of presenting feedback on users. This thesis presents the design and evaluation of WalkNRide, a physical activity tracker for Google Android. Through a longitudinal field study of WalkNRide, we attempt to inquire into the factors that drive the adoption (or non-adoption) of the tool as well as the ways in which the use of the tool contributes towards habit formation.